Alexander the Great : A Very Short Introduction - Bowden, Hugh (New York Oxford University Press, 2014)
In 336 BC Alexander the Great became king of Macedon. During his twelve-year reign he conquered the Achaemenid Persian Empire, the largest to have yet existed, and in the process had a profound effect on the world he moved through. In this examination of his life and career, Hugh Bowden explores his cultural and historical legacy.
Include Illustrations, References and Index
Keywords: Greece -- Alexander, the Great, 356 B.C.-323 B.C